1993
DOI: 10.2307/2426125
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Native Grass Seedlings along a Topographic/Moisture Gradient in the Nebraska Sandhills

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 144.122.ABSTRACT.-This study examines the effect of differential survival of seedlings on the distribution of native grasses along topographic grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
(19 reference statements)
1
19
1
1
Order By: Relevance
“…This pattern suggests that germination and recruitment of grasses in the Monte desert may be largely restricted to exceptional summers when rainfall surpasses a certain threshold, as implied by Neilson (1986), Westoby et al . (1989) and Potvin (1993) for other semiarid regions. Bouteloua eriopoda seedlings were observed in the northern Chihuahuan desert (USA) in only seven of the years between 1915 and 1968 (Neilson 1986) and oceanic disturbances like the North Pacific sea‐surface temperature (SST) anomalies may be needed to provide climatic conditions favourable for grass recruitment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This pattern suggests that germination and recruitment of grasses in the Monte desert may be largely restricted to exceptional summers when rainfall surpasses a certain threshold, as implied by Neilson (1986), Westoby et al . (1989) and Potvin (1993) for other semiarid regions. Bouteloua eriopoda seedlings were observed in the northern Chihuahuan desert (USA) in only seven of the years between 1915 and 1968 (Neilson 1986) and oceanic disturbances like the North Pacific sea‐surface temperature (SST) anomalies may be needed to provide climatic conditions favourable for grass recruitment.…”
Section: Discussionmentioning
confidence: 95%
“…This evidence is, however, circumstantial and should be considered with caution as the measurement of both facilitation and competition on seedling dynamics requires careful experimentation (Aguiar et al . 1992; Potvin 1993; Defossé et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Water stress is a key factor limiting seedling establishment in many communities (Potvin 1993;Lauenroth et al 1994;Kolb and Robberecht 1996;Wilson and Witkowski 1998;Weltzin and McPherson 2000), and rapid growth and the development of extensive root systems are well-established traits enabling seedlings to access resources in both water and nutrient limited soils (Orians and Solbrig 1977;Chapin 1980;Caldwell and Richards 1986). This may be particularly important in grassland regions where transpiration demands are high (Hayden 1998).…”
Section: Introductionmentioning
confidence: 99%
“…While no-till drills have helped solve seeding problems, weed control remains one of the biggest obstacles to establishing native grasses. The most critical part of the native grass life cycle is the seedling stage, with events during this life stage having profound effects on competition and community structure (Potvin 1993). McKenna et al (1991) found that many native grasses are slow to establish and are vulnerable to weed competition during the seedling stages.…”
Section: Introductionmentioning
confidence: 99%